Encyclopedia of energy engineering and technology - Capehart, B. L. (CRC Press, 2007)
Using limited resources in sustainable ways, energy engineers and technologists have made people's lives comfortable and affordable with efficient and cost-effective technology, from air conditioners to waste fuels. But to accommodate the expanding world population, the global supply of energy has been increasingly strained. Energy efficiency, energy conservation through energy management, and the use of renewable energy sources are three of the major strategies that can provide the energy and energy services for the world's population and economy. Energy managers, researchers, scholars, and po.